Dinamika Pemikiran Hukum Islam di Malaysia - Riza, Achmad Kemal (Islamic Family Law Department, Sharia and Law Faculty, UIN Sunan Ampel Surabaya, Indonesia, 2013)
The dynamics of Islamic legal thought in malaysia is a contestation of conservatism, moderatism and that of liberalism. When the opposition party of PAS promote conservatism and accuse the government to be not-islamic, UMNO the ruling party responded by launching serial of Islamic campaign. The government try to promote a modern and modern Islam by introducting Islamic Banks, establishing JAKIM to develop modern understanding and application of Islam in Malaysia, hosting an International Islamic Uniersity of Malaysia. Plenty of Muslim intellectuals and clerics were admissed as employees in these institutions. Among the product of this campaign is the enactment of Islamic law act in 1984 for Federal Territory which was reasonably progressive. Thus, criticism from the opposition remains and lead the government to lean toward conservatism. On the other hand, liberal thought of Islam, which in the area of Islamic family law was boosted by gender equality as represented by Sisters in Islam (SIS), also actively engage in discussion and try their best to influence the government policy on Islamic family law with the help of their international exposure.